Sistem Pakar Diagnosis Stunting pada Balita Menggunakan Metode Forward Chaining dan Logika Fuzzy Sugeno - Ananda, Putri Rizky; Sriani, Sriani (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Stunting is still a serious problem for children in Indonesia. In one area, especially Batubara Regency at the Pematang Panjang Community Health Center, in this area treatment for this disease must continue. This research was carried out with the aim of making stunting diagnosis more easily using the WEB site. By applying the Forward Chaining method and Sugeno's Fuzzy Logic. Based on the research results, it appears that Forward Chaining is a livelihood method that begins with fact analysis, while Sugeno's Fuzzy Logic can determine its ability to provide disease diagnoses. Based on 122 data on stunted toddlers obtained, the final diagnostic results showed that there were 106 data on toddlers who were declared stunted and 16 toddlers who were declared normal. From the 122 data, data was obtained with details of toddlers being at risk of stunting at a high level of (57%), followed by a very high risk level for stunting (26%) and a low risk level for stunting (17%).